Demographics and Histopathological Characteristics of Lung Cancer Patients in Cirebon District, Indonesia (2021-2023) - Sulaeman, Syakira Puteri; Fitrie, Alya Amila; Sedayu, Sedayu (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Based on the Global Burden of Cancer Study (GLOBOCAN) in 2020, In the world, lung cancer is the first cause of death. In Indonesia, lung cancer is the third highest. Lung cancer is classified into two cell types: Small Cell Lung Cancer and Non-Small Cell Lung Cancer. There are two types of Non-Small Cell Lung Cancer: squamous cell carcinoma, adenocarcinoma, and large cell carcinoma. Aims: To determine the demographics and histopathological characteristics of lung cancer patients in Cirebon District (2021-2023). Methods: This research employed a descriptive observational method. The data were collected from general hospitals’ medical records of lung cancer patients at RSUD Waled Cirebon and RSUD Arjawinangun in 2021-2023 using the total sampling technique. There were 69 respondents met the inclusion criteria for this recent study. Results: In this study, there were 68.1% of patients aged from 46 to 70 years, and the majority were male (66.7%). The most common cancer cell type was adenocarcinoma (69.6%). Most patients did not have information regarding occupational data (68.1%), smoking history (98.6%), family history (98.6%), and staging (89.9%) included in their medical records. Conclusion: The analysis showed that most lung cancer patients are aged 46-70 years and male incidences in lung cancer patients were higher. The most common type of histopathological is adenocarcinoma. Related to occupational data, smoking history, family history, and staging could not be concluded because they were not included in the medical record. Received: 25 September 2024 | Reviewed: 19 October 2024 | Revised: 30 November 2024 | Accepted: 12 December 2024.